Social support score in patients with malignant diseases—with sociodemographic and medical characteristics - Corovic, Snezana; Vucic, Veroljub; Mihaljevic, Olgica; Djordjevic, Jelena; Colovic, Sofija; Radovanovic, Snezana; Radevic, Svetlana; Vukomanovic, Ivana Simic; Janicijevic, Katarina; Sekulic, Marija; Djukic, Svetlana; Vukomanovic, Vladimir; et al. (Frontiers in Psychology, 2023)
Introduction Social support as a complex construct has a positive influence not only on a patient’s condition but also on the process of the patient’s emotional adjustment to cancer. The goal of this study is to investigate aspects of the level of social support in oncology patients and its interconnection with sociodemographic and medical variables. Method The study was conducted as a prospective observational study in 2020, including 250 patients aged 19 and over, both sexes, with a diagnosis of oncological disease. The research was conducted in the Department of General Medicine of the Health Center Trstenik, Central Serbia, after approval by the Ethics Committee of the Health Center Trstenik, Central Serbia. A social support assessment questionnaire (Oslo-3 Social Support Scale) was used as a research instrument. Results Data collected from the entire study population showed that bad social support was present in almost 90% of cases. Univariate and multivariate regression analysis showed a statistically significant influence of the following variables on the bad social support: education level, activity limitation, difficulties in performing daily activities, the impact of pain on the performance of activities, the need for additional help with activity, the need for help at home, unfulfilled needs for health care, means of information, anxiety score and depression score. Conclusion Interventions to increase social support may be important for enhancing mental health and quality of life in cancer patients.